A paradigm shift in mathematical physics, Part 3: A mirror image of Feynmans quantum electrodynamics (QED) - Boyd, Jeffrey H. (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
Richard Feynmans book QED, written for a lay audience, is a trusted source of information about Quantum Electro-Dynamics by a Nobel laureate. It is a mirror image of the Theory of Elementary Waves (TEW), discovered by Lewis E. Little. Recent work on TEW, published in this journal, shows that an elementary ray has the shape of a cylindrical helix traveling in Euclidean space, with a complex amplitude. This is an analog in physical nature of Feynmans mathematical concept of an amplitude, which is the core of QED. The only substantial difference is that an amplitude is assumed by Feynman to travel in the same direction as the particle, but in TEW they travel in opposite directions. There is almost no empirical data to resolve that disagreement. Such evidence as exists favors the idea they travel in opposite directions. If we modify Feynmans QED in this way we end up with a theory symmetrical to QED. We nickname it QÆD, using the letter Æ to symbolize an ælementary ray. QÆD is a fountain of information about the nature of elementary rays, and resolves some of the problems that Feynman said he found in QED.